2019
DOI: 10.4102/jamba.v11i2.692
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of flood vulnerability and adaptation: A case study of Hamutsha-Muungamunwe village, Makhado municipality

Abstract: This study assesses flood vulnerability, levels of vulnerability, determinants of flood vulnerability and coping strategies for flood hazards. The vulnerability and resilience of the local communities are key concepts in this study. Most households are vulnerable to flood hazards. It is therefore important to measure their levels of vulnerability and assess their responses for current and future planning. A flood vulnerability index was used to measure the extent of flood vulnerability. Key informant interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 13 publications
3
31
2
Order By: Relevance
“…Several theoretical frameworks for vulnerability assessment were developed with different scales (local, national, global), components (exposure, susceptibility/sensitivity, capacity), and dimensions (social, economic, physical, environmental, institutional) depending on the research fields (for example [3,4,[24][25][26][27][28][29][30][31]). Multiple studies were conducted to assess rural flood vulnerability incorporating exposure, susceptibility, and capacity components, for example in Romania [32], Ghana [6], South Africa [33], Mozambique [34], Vietnam [8], India [10], Pakistan [11], and Bangladesh [35]. However, none of the frameworks or assessment studies clearly revealed the impact of the rural floods or other rural hazards on the interaction/linkages between spatial units (rural and urban) and its influences on the vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical frameworks for vulnerability assessment were developed with different scales (local, national, global), components (exposure, susceptibility/sensitivity, capacity), and dimensions (social, economic, physical, environmental, institutional) depending on the research fields (for example [3,4,[24][25][26][27][28][29][30][31]). Multiple studies were conducted to assess rural flood vulnerability incorporating exposure, susceptibility, and capacity components, for example in Romania [32], Ghana [6], South Africa [33], Mozambique [34], Vietnam [8], India [10], Pakistan [11], and Bangladesh [35]. However, none of the frameworks or assessment studies clearly revealed the impact of the rural floods or other rural hazards on the interaction/linkages between spatial units (rural and urban) and its influences on the vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…The model was called vulnerability. Birkmann (2006) defined the broad and multidisciplinary view of vulnerability (Munyai et al 2019;Pricope et al 2019b). According to the study, indicators, and criteria used for vulnerability measurement should have a physical, economic, and social relationship with the area of interest (Sadeghi-Pouya et al 2017;Yalcin and Akyurek 2004).…”
Section: Vulnerability Assessment Methods and A Brief Discussion On Pmentioning
confidence: 99%
“…Climate is recognized by the municipality to be changing, altering and resulting to rising temperature and reduced and erratic rainfall across the district, which is a reflection of the regional climate [58,75]. The new climate pattern according to the district Integrated Development Plan has caused reduction of access to potable water, food security threats and increase health effects to poverty stricken communities [72].…”
Section: Climate Of Mopani Districtmentioning
confidence: 99%